Development of prune jelly containing Bacillus clausii (Research, Society and Development, 2023)
Probiotic dairy products are widely consumed, but in view of the growing number of vegan and lactose-intolerant individuals, the elaboration of probiotic foods of plant origin is an option. Thus, the objective was to develop prune jelly containing Bacillus clausii and to evaluate the physical-chemical, microbiological characteristics and the resistance of the probiotic to in vitro digestion. Prune jellies containing 108 spores/g of B. clausii and control jellies were prepared and stored at 8°C for 45 days. Physical-chemical analyzes of pH, acidity, aw, phenolic compounds and color and microbiological analyzes of the viability of B. clausii in the product, Salmonella spp., filamentous fungi and yeasts, Enterobacteriaceae, in addition to the in vitro test of survival of the microorganism to digestion by gastrointestinal tract were performed. The presence of bacteria in the product did not interfere with its physicochemical characteristics. B. clausii showed a viability of 7.64 Log CFU/g at the beginning and end of the shelf life of the jellies, with no significant variation between the times studied. The product was suitable for consumption, with microbiological quality within the standards of the legislation. At the end of the in vitro digestion test, at time 0, B. clausii presented an average count of 7.57 Log CFU/g and at 45 days 7.30 Log CFU/g, with a survival rate at both times > 95 %. The prune jelly was an excellent matrix to carry B. clausii, which showed an excellent survival rate in the product, which can be considered a potentially probiotic food.